FIGURE 108 in Grenadiers (Teleostei: Gadiformes: Macrouridae) of Japan and adjacent waters, a taxonomic monograph - Nakayama, Naohide (Zenodo, 2020)
FIGURE 108. Preserved specimen of Coryphaenoides filifer. HUMZ 126365, 92.5 mm HL, 506+ mm TL, northwest of Shiretoko Peninsula, Hokkaido, Okhotsk Sea, 1348 m depth. (A) Lateral view; (B) dorsal and (C) ventral views of the head and trunk. [Photos: N. Nakayama] Published as part of Nakayama, Naohide, 2020, Grenadiers (Teleostei: Gadiformes: Macrouridae) of Japan and adjacent waters, a taxonomic monograph, pp. 1-383 in Megataxa 3 (1) on page 165, DOI:10.11646/megataxa.3.1.1, http://zenodo.org/record/6422776